What is a compound? The main criteria for compoundhood - Altakhaineh Abdel Rahman Mitib (ExELL (Explorations in English Language and Linguistics))
This study aims to identify the main cross-linguistic criteria for compoundhood discussed in the relevant literature, with a special focus on English, ranking them from the most reliable to the least. These criteria - orthographic, phonological, syntactic and semantic in nature - have been proposed to make a distinction between compounds and phrases. The analysis reveals that the most reliable cross-linguistic criteria to distinguish between phrases and compounds are adjacency and referentiality. With regard to the former criterion, no intervening elements can be inserted between the head and the non-head of compounds, whilst such insertion is allowed in phrases. With regard to the latter criterion, the non-head of a phrase is always referential, whereas the non-head of a compound is normally non-referential. Other criteria have been found to be partially applicable, e.g. free pluralisation of the non-head, compositionality, stress, possibilities for modification and coordination, ellipsis, orthography and the replacement of the second element by a pro-form. The study also proposes a definition for compounds that may be the most widely applicable. Finally, the study concludes with ranking the main criteria for compoundhood discussed in the study.